THE IMPACT OF PROFITABILITY, CAPITAL STRUCTURE AND OPERATING CASH FLOW TO STOCK RETURN (EMPIRICAL STUDY OF BANKING COMPANIES LISTED IN INDONESIA STOCK EXCHANGE FOR THE YEAR 2012-2014) - Malkan, Reyhan Ilyas (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This research purpose to find the impact of profitability, capital structure and operating cash flow on stock returns for banking companies listed in Indonesian Stock Exchange. Population used in this research is 42 companies and then through the purposive sampling process, this research found 28 companies from Indonesia stock exchange that can fulfill the sampling criteria. Multiple regression analysis is used as the technique to test the hypothesis. Results of hypothesis testing concluded that the profitability has a positive impact to stock return. Then, the operating cash flow has a same result that has significant positive impact on stock return. However, this study cannot prove that capital structure possessed has significant influence on stock return in banking companies. In this research, it is found that profitability with the ratio of earnings per share is a strong indicator that can impact significantly on stock returnsKey word: stock return, profitability, capital structure, operating cash flow.